Legal Status of NGOs in the United Nations Economic and Social Council: (Analytical study) - Hussain, Ako Hamdamin; Abdulkarim Baban, Bryar Sheko (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
This research studies the legal status of Non-Governmental Organizations (NGO) in United Nations, especially in the Economic and Social Council, while these organizations participate in the acts of the Economic and Social Council. This participation is not compulsory, in other words that the source of this participation is the single will, and the request of NGOs for this status, and once NGOs have gained consultative status, they are bound by limited duties and obligations. The Economic and Social Council gives the consultative status to NGOs, and this status is divided into three types, namely: first, the general consultative status for international NGOs is relatively large and well-established and carries out its activities in a wide geographical area. Second, the special consultative status is granted to NGOs that are smaller and recently created. Third, Roster, it is for all NGOs ready to consult when requested by the Council or its subsidiary bodies.